Implementasi Pendidkan Seni Budaya dan Prakarya Berbasis Kearifan Lokal dalam Membentuk Karakter (Studi Kasus Siswa SDN Gedeh 3 Warungkondang) - Maman Suherman; Suharyanto H. Soro; Badri Zaman; Nelly Amalia; Ira Setiani (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
Character education plays an important role in shaping students' personalities with integrity, morality and independence, especially in facing the challenges of globalization that often erode local cultural heritage. However, the implementation of local wisdom-based character education in Arts, Culture and Crafts (SBDP) learning at the elementary school level faces quite significant challenges, including the lack of integration between educational content and local cultural values. In other words, this study highlights the importance of a local wisdom-based approach in bridging academic learning with character education while preserving cultural heritage. The findings recommend its implementation as a practical and sustainable strategy to develop the intellectual and moral capacity of elementary school students. This study aims to (1) find and describe the implementation of local wisdom-based character education through Arts, Culture and Crafts learning of SDN Gedeh 3 students and (2) identify obstacles and strategies to optimize its implementation in Arts, Culture and Crafts learning. This study uses a case study approach with a qualitative method. The research findings show that (1) the implementation of Arts, Culture and Crafts learning can shape students' character; (2) This integration not only improves students' understanding of SBDP material but also strengthens their cultural identity and appreciation of local traditions.